Staged Custom, Intramedullary Antibiotic Spacers for Severe Segmental Bone Loss in Infected Total Hip Arthroplasty - Atul F. Kamath; Okechukwu Anakwenze; Gwo-Chin Lee; Charles L. Nelson (Advances in Orthopedics)
Introduction. Total hip arthroplasty (THA) infections with severe bone loss pose significant reconstructive challenges. We present our experience with two-stage hip reimplantation using an intramedullary, antibiotic-impregnated nail. Methods. Three patients with infected THA with severe proximal femoral bone loss (Mallory type IIIB or greater) were treated using a custom antibiotic spacer. Clinical outcomes and any complications were recorded. Average followup was 49 months from final reimplantation. Results. Mean age at spacer placement (stage 1) was 53 years. The mean Harris Hip Score at final followup was 80. Two patients had asymptomatic heterotopic ossification, and one patient had a 2 cm leg-length discrepancy. Conclusions. A custom intramedullary nail antibiotic spacer is a reliable option in the staged management of the infected THA with severe proximal femoral bone loss. Benefits of this technique include limb salvage with maintenance of leg length, soft tissue tension, and functional status.